Employment Termination in the Middle of Covid-19 Pandemic: Labor Law Point of View - Aris Prio Agus Santoso; Erna Chotidjah Suhatmi (Universitas Kuningan, 2021)
Article 28D paragraph (2) of the 1945 Constitution states everyone has the right to work and to receive fair and proper compensation and treatment in a working relationship. It is emphasized in Article 151 (1) of Law no. 13/2003 concerning Manpower. The entrepreneurs, workers/laborers, trade/labor unions, and the government must make every effort to prevent an employment termination. In fact, many workers have been terminated and some even did not receive any severance pay at all. Accordingly, the researchers formulated the following research questions: how to terminate employment in the midst of the Covid-19 pandemic, and how is the government’s responsibility for the welfare guarantees for workers. This research employed a normative juridical approach by collecting data from literature studies. The data obtained were analyzed qualitatively. The findings revealed the layoffs in the midst of the Covid-19 pandemic were a breach of contract by entrepreneurs. The entrepreneurs were still obliged to provide severance pay, reward money, and compensation money. In addition, the government has also provided accountability in the form of an economy, the Pre-Work Card. With this card, workers can develop workforce competence, increase productivity and competitiveness of the workforce, and develop entrepreneurship. The Manpower Office responsible for this program also participated in the workforce supervising and guiding